Repurposing the oncolytic virus VSV∆51M as a COVID-19 vaccine - Alkayyal, Almohanad A.; Darwish, Manar; Ajina, Reham; Alabbas, Saleh Y.; Alotaibi, Mohammed A.; Alsofyani, Abeer; Bokhamseen, Maha; Hakami, Maumonah; Albaradie, Omar A.; Moglan, Abdulaziz M.; Hala, Sharif; Alsahafi, Abdullah Faisal; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
The coronavirus disease 2019 (COVID-19) pandemic imposes an urgent and continued need for the development of safe and cost-effective vaccines to induce preventive responses for limiting major outbreaks around the world. To combat severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), we repurposed the VSV∆51M oncolytic virus platform to express the spike receptor-binding domain (RBD) antigen. In this study, we report the development and characterization of the VSV∆51M-RBD vaccine. Our findings demonstrate successful expression of the RBD gene by the VSV∆51M-RBD virus, inducing anti-RBD responses without attenuating the virus. Moreover, the VSV∆51M-RBD vaccine exhibited safety, immunogenicity, and the potential to serve as a safe and effective alternative or complementary platform to current COVID-19 vaccines.